SOCIAL CAPITAL AND DISPARITIES IN CANADIAN YOUTH’S MATHEMATICS ACHIEVEMENT - Bassani, Cherylynn (Canadian Journal of Education/Revue canadienne de l’éducation, 2008)
This article examines the influence of youth’s family and school contexts in order to understand disparities in Canadian youth’s mathematics achievement. Using hierar‐ chical linear analysis, some of the main assumptions of social capital theory are tested using the Canadian data from the 1999 Programme for International Student Assess‐ ment. Findings revealed that many family‐school contextualized effects were not sig‐ nificant, suggesting that researchers need to look at the conceptualization and opera‐ tionalization of social capital. Relationships between family structure and some measures of school social and were, however, found to be significant. Results suggest that the similarity hypothesis needs to be further analyzed and perhaps integrated into social capital theory. Key words: family, school, PISA, booster effect, double jeopardy effect, mitigating effect Dans cet article, l’auteure analyse les influences des contextes familiaux et scolaires dans lesquels les jeunes évoluent en vue de comprendre comment ces contextes créent des disparités dans les résultats qu’ils obtiennent en mathématiques. Utilisant des données canadiennes tirées du Programme international pour le suivi des acquis des élèves (PISA) de 1999, l’auteure a testé ses hypothèses à l’aide d’une analyse linéaire hiérarchique. Ses résultats révèlent qu’un grand nombre des effets contextualisés familiaux et scolaires n’étaient pas statistiquement significatifs, ce qui donne à penser que les chercheurs doivent se pencher sur la conceptualisation et l’opérationalisation du capital social. Certaines relations entre la structure familiale et diverses mesures du capital social et humain dans les écoles se sont toutefois avérées significatives. Les résultats semblent indiquer que l’hypothèse de similarité a besoin d’être analysée davantage et peut‐être intégrée dans la théorie du capital social. Mots clés : famille, école, PISA, effet stimulant, effet double obstacle, effet atténuant